Design of an artificial language for Human-Computer interaction. - García-González, Jorge (My University, 2017)
This project has as objective to note motivations to search and develop an optimal general purpose artificial language with effective and not ambiguous human-machine communication objective in long term. Following this idea, we will ask ourselves how could be studied which languages basic elements are actually necessaries and which ones are unnecessary or even counter-productive. Given the optimality objective that motivates this works, it will be necessary to face general purpose language from a constructive way (from the absence of language, creating them progressively). This work does not aim to face an specific natural language understanding so we will not study human language capacity complexities and we will not subdue our resulting languages to match with any natural language. With that, we will use as study subject three basics elements in natural languages (subject, verb and object). We will propose an enough simple clustering problem performed by agents with partial information that will be shared between them by the use of non ambiguous languages with increasing complex syntax, semantic and use. We will also define some mathematical tools to evaluate results to contrast each language effectiveness to obtain results to empirically support what language is better to face proposed problem.
Diseño de un lenguaje artificial para la interacción Hombre-Máquina.
TFG presentado en inglés
Keywords: Interacción hombre-ordenador; Lenguaje natural (Informática); Informática - Trabajos Fin de Grado; Grado en Ingeniería Informática - Trabajos Fin de Grado; Lenguajes,; lenguajes artificiales,; agrupamiento,; sistema multiagente.